Expropriation Of Minority Shareholders: A Study Of Familyowned Firms In Malaysia - Lim, Boon Leong (2013)
Based on a balance panel data of 191 family-owned public companies listed on the Main Board of Bursa Malaysia between 2002 and 2007, this study examines whether minority shareholders have been expropriated by executive directors via the setting of directors’ remuneration. It also seeks to determine which component of directors’ remuneration has been used as the means of expropriation; and at which managerial ownership levels has expropriation taken place. Examination of these research problems is based on the premise of managerial power theory which predicts the occurrence of expropriation given the characteristics of family-owned firms in Malaysia. Among those characteristics that provide the incentives for expropriation include divergence of cash flow and control rights, involvement of controlling shareholders in the firm management, and the presence of family members in the board of directors. The regression analysis shows that salary has been used as the means of expropriation between managerial ownership levels 23 – 76%. The occurrence of expropriation at this medium ownership level is due to the managerial entrenchment effect postulated by managerial power theory. Nevertheless at managerial ownership levels below 23% (low level) and above 76% (high level), the alignment of interest effect associated with managerial ownership brings about a lower level of salary paid to executive directors. Hence there is a non-linear relationship between directors’ salary and managerial ownership by using the fixed effect regression model.